Queerness is a particular liability: Feeling rules in college and university LGBTQ centers - Mandala, Chad R.; Ortiz, Stephanie M. (Journal of Homosexuality, 2023)
Organizational sociologists argue that informal and formal rules within workplaces function to increase employee productivity and effectiveness, but can also have negative emotional consequences. Feeling rules, which are the emotional norms that regulate interpersonal interactions within the workplace are not applied equally; white women and professionals of color are expected to display deference in the face of emotionally-charged experiences at work, while their counterparts are given more flexibility in how they could display anger or annoyance. Scholars note that feeling rules work to reproduce extant gendered and racial hierarchies when expectations regarding worker productivity, effectiveness and outcomes are restricted on the basis of social identities. Analyzing sixteen semi-structured interviews with LGBTQ Center staff, we demonstrate the feeling rules are organized around employees’ ability to (1) (re)produce trauma in themselves during training sessions and (2) minimize students’ and their own anger throughout the workday. © 2021 Taylor & Francis Group, LLC.
Keywords: LGBTQIA2+; amériques; approches et analyses; discipline; intersectionnalité; minorités sexuelles; projet charge mentale; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail émotionnel; états-unis

Les femmes noires qui aiment les femmes : résistances aux rapports de pouvoir enchevêtrés - Almeida, Jade (Université de Montréal, 2022)
« Les femmes noires qui aiment les femmes : résistance aux rapports de pouvoir enchevêtrés » aborde les questions de survie d’un point de vue queer et diasporique. Cette thèse soutient que les pratiques et positionnements au quotidien des participantes se situent dans les failles d’un système qui criminalise l’existence même des personnes noir.e.s. L’analyse des conditions de vie de ces femmes permet de mieux comprendre le panorama complexe des systèmes de pouvoir à l’intersection des rapports de classe, de genre, de race et de l’hétéropatriarcat. Elle permet également de reconnaitre leur capacité à créer un espace alternatif, un univers des possibles qui s’oppose aux catégories normatives et hégémoniques. Les réalités des participantes génèrent donc des points de départ où l’altérité devient outil de pensée critique, moyen de résistance et fondement d’un futur substantiellement différent infusé par l’espoir de l’amélioration. Cette recherche se base sur l’autoethnographie, une ethnographie de la participation et des entretiens semi-dirigés de 22 personnes qui s’identifient comme femmes, noires et ayant des rapports sexo-affectifs avec d’autres femmes. Cette thèse porte donc sur le désir et s’appuie sur de multiples apports, majoritairement de théoriciennes racisées, qu’elles soient issues du milieu académique ou fassent partie de mon cercle privé. Elle est formée par de puissants récits, mais également par des silences tout aussi évocateurs, par une attention accrue au domaine du micro et à la description, par une autoethnographie de la participation et par la volonté de dépeindre sur quelques pages ne serait-ce qu’un extrait de la flamboyance de ces femmes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; afro-féminisme; amériques; approches et analyses; autoethnographie; canada; communauté; cours; diaspora africaine; discipline; désir; désir lesbien; femmes* noires; féminismes noirs; intersectionnalité; lesbianisme; militance; montréal; point de vue situé; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; sociologie; thématiques

« Racisme, sexisme, homophobie, quelle carte tu veux ? » L’expérience post-migratoire des personnes LGBTQ du Nord global et du Sud global - de Sousa, Barbara Andrade; Chamberland, Line (Alterstice, 2021)
Cet article examine l’histoire de vie de sept immigrants ou immigrantes LGBTQ, originaires du Nord et du Sud global, qui habitent à Montréal. Les recherches sur l’immigration ont longtemps été réalisées selon un cadrage hétéronormatif, ce qui met à l’écart toute une série de questions relatives à l’impact de l’orientation sexuelle et de l’identité de genre non normative sur l’expérience migratoire. Les sociétés imposent des contraintes distinctes vis-à-vis des personnes LGBTQ. Une fois installées dans la société d’accueil, ces sujets peuvent expérimenter plus de possibilités sur le plan sexuel ; néanmoins leur origine peut devenir un marqueur qui les place à l’intérieur d’un rapport de pouvoir avec le groupe majoritaire. Notre article vise à mettre en lumière la manière dont les immigrants LGBTQ construisent leurs histoires de vie dans un contexte où leur vécu est traversé par l’imbrication de plusieurs aspects identitaires comme l’orientation sexuelle, l’identité de genre, l’ethnicité et la religion, pour n’en nommer que quelques-uns. L’approche intersectionnelle rend possible l’identification des systèmes de pouvoirs contraignants auxquels les participants font face quotidiennement. L’analyse thématique nous a permis d’être à l’écoute des individus afin de connaître les catégories de pouvoir et les systèmes d’oppression dont ils parlent — le but étant de positionner les répondants comme des sujets connaissants, et non de simples objets d’étude. L’analyse des entrevues montre que les individus LGBTQ qui expriment une combinaison variée d’identités affrontent des défis spécifiques liés au parcours migratoire.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; migration; montréal; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; systèmes d'oppressions; thématiques; violences

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge international handbooks, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Une « histoire du féminisme latino-américain depuis une position subalterne ». Entretien avec Y. Espinosa-Miñoso - Espinosa-Miñoso, Yuderkys (CONTRETEMPS, 2019)
Yuderkys Espinosa-Miñoso est une penseuse, écrivaine, chercheuse, enseignante et activiste féministe antiraciste et décoloniale d’origine afrodominicaine. Elle prépare un doctorat en philosophie à l’Université de Buenos Aires sur la “critique de la raison féministe latinoamericaine” sous la direction de Maria Lugones. Elle est membre fondatrice du Groupe Latino-américain d’Etude, de Formation et d’Action Féministe (GLEFAS).
Keywords: LGBTQIA2+; afro-féminisme; antiracisme; approches et analyses; cours; discipline; féminisme afrocarabéen; féminisme décolonial; féminisme latinoaméricain; histoire et politique; intersectionnalité; militance; philosophie; pol4212; premier cycle; sciences humaines; thématiques

Rapport sur le racisme vécu par la communauté LGBTQ+ montréalaise - Almeida, Jade (Conseil Québécois LGBT, 2017)
Le 18 août dernier, nous avons soumis au Ministère de l’Immigration, de la Diversité et de l’Inclusion (MIDI) un projet en réponse à l’appel pour réaliser une Consultation sur le racisme systémique afin que la Commission tienne notamment compte de l’intersection entre le racisme et les LGBTphobies dans ses consultations. Notre proposition a été acceptée selon le premier mandat qui avait été choisi par le ministère. En dépit de l’évolution de ce dernier, le Conseil québécois LGBT a souhaité poursuivre la mission qu’il s’était donnée à savoir mener une consultation sur le racisme systémique en lien avec les communautés LGBTQ+. Ce document en est la synthèse. Ainsi, pour la réalisation du présent rapport, nous avons recueilli 25 témoignages individuels. Toutes les personnes interviewées ont été victimes de racisme, certaines après avoir été témoin et être intervenues. Les 25 personnes entendues font partie de la communauté LGBTQ+ et sont racisées. Autant que faire se peut, nous avons essayé de recevoir des personnes représentant une grande diversité d’identités de genres et des sexualités. Sur la totalité des témoignages, nous avons donc pu nous entretenir avec des personnes s'identifiant comme lesbiennes, trans, bisexuelles, queers, gaies, studs ou encore pansexuelles.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; intersectionnalité; justice sociale; militance; montréal; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sex2283; sociologie; systèmes d'oppressions; thématiques; violences

Arts visuels - Foucher Zarmanian, Charlotte (Encyclopédie critique du genre : corps, sexualité, rapports sociaux, 2016)
"Arts visuel" est l'un des soixante-six textes thématiques de cette encyclopédie explorent les reconfigurations en cours des études de genre. Trois axes transversaux organisent cette enquête collective: le corps, la sexualité, les rapports sociaux. Les inégalités liées au genre sont de plus en plus envisagées en relation avec celles liées à la classe sociale, la couleur de peau, l'apparence physique, la santé ou encore l'âge. Cette approche multidimensionnelle des rapports sociaux a transformé radicalement les manières de penser la domination au sein des recherches sur le genre. En analysant les concepts, les enquêtes empiriques et les débats caractéristiques de ces transformations saillantes, les contributrices et contributeurs de cet ouvrage dessinent une cartographie critique des études de genre en ce début de XXIe siècle.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; encyclopédie; europe; fem1000; france; genre; histoire; identité sexuelle; identités LGBTQIA2+; intersectionnalité; occident; outils; premier cycle; recherche en milieux de pratique; ressource en ligne; régions géographiques; sciences humaines; sexualité; thématiques

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Multiple identities and crime: A study of Antillean women and girls in the Netherlands - Althoff, Martina (European Journal of Criminology, 2013)
The concept of intersectionality refers to the constructionist approach, which considers gender, class and race as categories of social inequality that cannot be added together but that intersect and construct each other. Social categories construct the social identities that affect what motivates people and how they operate. The question is how multiple identities come together in the context of crime? The paper reports the findings of a qualitative study that explored the concept of intersectionality when analysing crime. The study analysed the court files of Antillean women and girls living in the Netherlands and tried to find an explanation for their crime patterns in their struggle with their identity.
Keywords: LGBTQIA2+; antilles; approches et analyses; criminologie; discipline; europe; femmes* immigrantes; genre; identités; identités LGBTQIA2+; intersectionnalité; inégalités; pays-bas; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; étude qualitative

Feminist, queer, crip - Kafer, Alison (Indiana University Press, 2013)
Select all Front Matter (pp. i-vi) Front Matter (pp. i-vi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.1 Table of Contents (pp. vii-viii) Table of Contents (pp. vii-viii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.2 Acknowledgments (pp. ix-xii) Acknowledgments (pp. ix-xii) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.3 Textual Description of the Cover Art (pp. xiii-xvi) Textual Description of the Cover Art (pp. xiii-xvi) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.4 Introduction: Imagined Futures (pp. 1-24) Introduction: Imagined Futures (pp. 1-24) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.5 I have never consulted a seer or psychic; I have never asked a fortune-teller for her crystal ball. No one has searched my tea leaves for answers or my stars for omens, and my palms remain unread. But people have been telling my future for years. Of fortune cookies and tarot cards they have no need: my wheelchair, burn scars, and gnarled hands apparently tell them all they need to know. My future is written on my body. In 1995, six months after the fire, my doctor suggested that my thoughts of graduate school were premature, if not misguided. He... 1 Time for Disability Studies and a Future for Crips (pp. 25-46) 1 Time for Disability Studies and a Future for Crips (pp. 25-46) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.6 What would it mean to explore disability in time or to articulate “crip time”? Temporal categories are already commonly used in formulations of disability; one aspect of cripping time might simply be to map the extent to which we conceptualize disability in temporal terms. The medical field in particular has a long tradition of describing disability in reference to time. “Chronic” fatigue, “intermittent” symptoms, and “constant” pain are each ways of defining illness and disability in and through time; they describe disability in terms of duration. “Frequency,” “incidence,” “occurrence,” “relapse,” “remission”: these, too, are the time frames of symptoms, illness,... 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) 2 At the Same Time, Out of Time: Ashley X (pp. 47-68) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.7 In thinking about crip futurity, I find myself haunted by Ashley X. Born in 1997, the girl known as Ashley X was diagnosed with “static encephalopathy” a few months after her birth. “In the ensuing years,” doctors note, “her development never progressed beyond that of an infant,” and her doctors held no hope that her cognitive or neurological baseline would improve.¹ “At the age of 6 years, she [could] not sit up, ambulate, or use language.”² Concerned about their daughter’s long-term future, Ashley’s parents met with doctors in 2004 to discuss the potential effects of puberty and physical growth on... 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) 3 Debating Feminist Futures: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians (pp. 69-85) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.8 The pervasiveness of prenatal testing, and especially its acceptance as part of the standard of care for pregnant women, casts women as responsible for their future children’s able-bodiedness/able-mindedness; prospective parents are urged to take advantage of these services so as to avoid burdening their future children with any disabilities.¹ This notion of “burdening” children finds an echo in the debate over same-sex marriage, with LGBT couples cast as selfish parents, placing their own desires over the physical and mental health of their children (and, by extension, of all children). Moreover, according to Timothy Dailey of the Family Research Council, homosexual... 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) 4 A Future for Whom? Passing on Billboard Liberation (pp. 86-102) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.9 “Super man,” the billboard exclaims, the unfamiliar gap between the two words emphasizing both the noun and its adjective. Below this phrase is the word “STRENGTH,” followed by the imperative “Pass It On.” At the bottom, in small print, runs the name and web address of the organization behind this public relations campaign: Values.com/Foundation for a Better Life. The “super man” referenced in the caption is, of course, the late Christopher Reeve, the white actor who starred in a series ofSupermanfilms in the 1980s before becoming a quadriplegic in a riding accident in 1995. A black-and-white photograph of... 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) 5 The Cyborg and the Crip: Critical Encounters (pp. 103-128) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.10 Controversy came quickly to the cyborg. In 1983,Socialist Reviewinvited several feminist theorists, among them Donna Haraway, “to write about the future of socialist feminism in the context of the early Reagan era.”¹ Haraway responded with “A Manifesto for Cyborgs,” framing the cyborg as a figure of feminist critique.² Her cyborg was a radical border-crosser, blurring the boundaries between human and animal, machine and organism, physical and non-physical.³ Such a cyborg, she argued, could “guide us to a more livable place,” an “elsewhere,” in which “people are not afraid of their joint kinship with animals and machines, not afraid... 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) 6 Bodies of Nature: The Environmental Politics of Disability (pp. 129-148) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.11 Although concern with the environment has long been an animating force in disability studies and activism, “environment” in this context typically refers to the built environment of buildings, sidewalks, and transportation technologies. Indeed, the social model of disability is premised on concern for the built environment, stressing that people are disabled not by their bodies but by their inaccessible environments. (The wheelchair user confronting a flight of steps is probably the most common illustration of this argument.) Yet the very pervasiveness of the social model has prevented disability studies from engaging with the wider environment of wilderness, parks, and nonhuman... 7 Accessible Futures, Future Coalitions (pp. 149-170) 7 Accessible Futures, Future Coalitions (pp. 149-170) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.12 When describing disability studies to my students, I often draw on Douglas Baynton’s insight that “disability is everywhere in history once you begin looking for it.”¹ For Baynton, “looking for it” entails not only recovering the stories of disabled people or tracing histories of disability discrimination but also exploring how notions of disability and able-mindedness/able-bodiedness have functioned in different contexts. Baynton issues his provocation to historians, but disability studies scholars in other fields have extended its reach, pushing their own colleagues to recognize disability as a category of analysis. Deeply influenced by and indebted to this work, I use this... Appendices (pp. 171-178) Appendices (pp. 171-178) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.13 Notes (pp. 179-224) Notes (pp. 179-224) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.14 Bibliography (pp. 225-252) Bibliography (pp. 225-252) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.15 Index (pp. 253-258) Index (pp. 253-258) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.16 Back Matter (pp. 259-259) Back Matter (pp. 259-259) https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctt16gz79x.17 Indiana University Press logo Front Matter Download XML Table of Contents Download XML Acknowledgments Download XML Textual Description of the Cover Art Download XML Introduction:: Imagined Futures Download XML Time for Disability Studies and a Future for Crips Download XML At the Same Time, Out of Time:: Ashley X Download XML Debating Feminist Futures:: Slippery Slopes, Cultural Anxiety, and the Case of the Deaf Lesbians Download XML A Future for Whom?: Passing on Billboard Liberation Download XML The Cyborg and the Crip:: Critical Encounters Download XML Bodies of Nature:: The Environmental Politics of Disability Download XML Accessible Futures, Future Coalitions Download XML Appendices Download XML Notes Download XML Bibliography Download XML Index Download XML Back Matter Download XML ABOUT US About JSTOR Mission and History JSTOR Labs JSTOR Daily News Webinars Careers EXPLORE CONTENT What's in JSTOR Advanced Search By Subject By Title Collections Publisher Images RESEARCH TOOLS Data for Research The JSTOR Understanding Series Constellate HELP CENTER Get Support Get Access LibGuides Research Basics Contact Us For Librarians For Publishers Teaching Resources JSTOR is part of ITHAKA, a not-for-profit organization helping the academic community use digital technologies to preserve the scholarly record and to advance research and teaching in sustainable ways.©2000‍–2024 ITHAKA. All Rights Reserved. JSTOR®, the JSTOR logo, JPASS®, Artstor®, Reveal Digital™ and ITHAKA® are registered trademarks of ITHAKA. Terms & Conditions of Use Privacy Policy Accessibility Cookie Policy Cookie Settings Description In Feminist, Queer, Crip Alison Kafer imagines a different future for disability and disabled bodies. Challenging the ways in which ideas about the future and time have been deployed in the service of compulsory able-bodiedness and able-mindedness, Kafer rejects the idea of disability as a pre-determined limit. She juxtaposes theories, movements, and identities such as environmental justice, reproductive justice, cyborg theory, transgender politics, and disability that are typically discussed in isolation and envisions new possibilities for crip futures and feminist/queer/crip alliances. This bold book goes against the grain of normalization and promotes a political framework for a more just world.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; approches et analyses; care; corps; cours; crip; discipline; future; identités LGBTQIA2+; intersectionnalité; justice sociale; philosophie; premier cycle; périodes historiques; queer; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1920; thématiques; études critiques du handicap

Réflexions autour de la notion d’homophobie: succès politique, malaises conceptuels et application empirique - Chamberland, Line; Lebreton, Christelle (Nouvelles Questions Féministes, 2012)
Après en avoir retracé rapidement la genèse, cet article rapporte les principales critiques adressées au concept d’homophobie, notamment son réductionnisme qui tend vers des explications de nature psychologique ainsi que l’éviction de la hiérarchie des sexes/genres. Nous discutons ensuite deux pistes théoriques permettant de contourner les limites précédemment identifiées. La première examine le potentiel de l’approche intersectionnelle. La seconde voie invite à une redéfinition du concept d’homophobie, lui reconnaissant une portée exclusivement descriptive, et non plus en tant que concept explicatif, justifiant ainsi sa subordination au concept d’hétérosexisme qui offre une perspective systémique. Nous examinons ces concepts en fonction de leur capacité à rendre compte de l’oppression des lesbiennes.
Keywords: 1900-1999; 1970-1979; 1980-1989; 2000 à aujourd'hui; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lesbianisme; phi2030; philosophie; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; états-unis

Sexe, race, classe pour une épistémologie de la domination - Dorlin, Elsa (Actuel Marx confrontation, 1158-5900, 2009)
La pensée féministe s'est historiquement attachée, depuis -- voire en dehors de -- la tradition matérialiste, à montrer que le rapport declasse n'épuise pas l'expérience de la domination vécue par les femmes et, plus généralement, par les minorités sexuelles. Plus encore, en élaborant des outils d'analyse tels que le mode de production domestique, les rapports sociaux de sexe ou le rapport de genre , la pensée féministe a travaillé sur l'imbrication des rapports de pouvoir, dénaturalisant la catégorie de sexe à l'aune de ses déterminations historico-sociales. Depuis quelques années en France, la réflexion sur l'imbrication des rapports de pouvoir s'est complexifiée davantage, notamment sous l'influence des travaux nord et sud-américains, mais aussi caribéens ou indiens. Les problématiques relatives aux identités sexuelles, aux régimes de sexualité, mais aussi celles qui articulent le genre et la nation, la religion et/ou la couleur, ont permis de développer un véritable champ de réflexion. La question cruciale de l'articulation du sexisme et du racisme, notamment, a ainsi renouvelé tout autant l'agenda des mouvements féministes que la recherche universitaire. Cet ouvrage a pour mais d'interroger les différents outils critiques pour penser l'articulation des rapports de pouvoir de sexe et de race ont-elles méthodologiquement le même statut que la classe ? À quelles conditions utiliser la catégorie decourse comme une catégorie d'analyse ? L'analyse en termes de classe a t-elle été éclipsée par l'analyse croisée du sexisme et du racisme, après les avoir longtemps occultés ?...) cet ouvrage discute les différents modes de conceptualisation de ce que l'on pourrait appeler l'hydre de la domination : analogique, arithmétique, géométrique, généalogique. À partir de différentes traditions disciplinaires (sociologie, science politique, philosophie, psychologie, littérature...), les contributions ici réunies présentent un état des lieux des diverses appréhensions de l'imbrication des rapports de pouvoir -- intersectionnalité , consubstantialité , mondialité , postcolonialité , ... et, ce faisant, (re)dessinent les contours d'une véritable épistémologie de la domination.
Keywords: LGBTQIA2+; approches et analyses; consubstantialité des rapports sociaux; cours; discipline; discours dominant; fem1000; féminisme décolonial; féminisme matérialiste; genre; identités LGBTQIA2+; intersectionnalité; premier cycle; projet charge mentale; rapports sociaux de sexe; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Femmes, genre, féminisme - Trat, Josette (Les cahiers de "Critique communiste", 2007)
"Le retour sur l'histoire du courant féministe "lutte de classes" met en évidence l'urgence à penser les rapports sociaux de sexe en les articulant aux rapports de classe et aux rapports Nord-Sud. Quels sont les apports et les limites du Queer pour penser le genre et les oppressions? Quels sont les rapports entre les mouvements féministes et les mouvements gais et lesbiens? Quels sont les effets de la mondialisation néolibérale sur l'oppression des femmes et sur leurs luttes à l'échelle mondiale? Les questions des rapports de classe et celle du racisme ont été également remises au-devant de la scène par la révolte des banlieues dont les filles semblaient toutefois singulièrement absentes. Pourtant, elles luttent contre le sexisme, ainsi que le montre le collectif Féminin-Masculin de Vitry. A l'heure où les retours en arrière sont toujours possibles, comme en atteste l'émergence d'un mouvement masculiniste, la construction d'un courant féministe se donnant pour objectif de changer radicalement la société reste nécessaire pour gagner l'égalité réelle entre hommes et femmes."
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; histoire et politique; intersectionnalité; militance; premier cycle; queer; rapports de classe; rapports sociaux de sexe; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme

Reinventing identities: the gendered self in discourse - Bucholtz, Mary; Liang, A. C.; Sutton, Laurel A. (Studies in language and gender, 1999)
Talk is crucial to the way our identities are constructed, altered, and defended. Feminist scholars in particular have only begun to investigate how deeply language reflects and shapes who we think we are. This volume of previously unpublished essays, the first in the new series Studies in Language and Gender, advances that effort by bringing together leading feminist scholars in the area of language and gender, including Deborah Tannen, Jennifer Coates, and Marcyliena Morgan, as well as rising younger scholars. Topics explored include African-American drag queens, gender and class on the shopping channel, and talk in the workplace.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; identités LGBTQIA2+; intersectionnalité; lin2685; linguistique; premier cycle; queer; ressource en ligne; sciences humaines; thématiques

Looking queer: body image and identity in lesbian, bisexual, gay, and transgender communities - Atkins, Dawn (Haworth Press, 1998)
Looking Queer: Body Image in Lesbian, Bisexual, Gay, and Transgender Communities contains research, firsthand accounts, poetry, theory, and journalistic essays that address and outline the special needs of sexual minorities when dealing with eating disorders and appearance obsession. Looking Queer will give members of these communities hope, insight, and information into body image issues, helping you to accept and to love your body. In addition, scholars, health care professionals, and body image activists will not only learn about queer experiences and identity and how they affect individuals, but will also understand how some of the issues involved affect society as a whole. Dismantling the myth that body image issues affect only heterosexual women, Looking Queer explores body issues based on gender, race, class, age, and disability. Furthermore, this groundbreaking book attests to the struggles, pain, and triumph of queer people in an open and comprehensive manner. More than 60 contributors provide their knowledge and personal experiences in dealing with body image issues exclusive to the gay and transgender communities, including: exploring and breaking down the categories of gender and sexuality that are found in many body image issues finding ways to heal yourself and your community discovering what it means to “look like a dyke” or to “look gay” fearing fat as a sign of femininity determining what race has to do with the gay ideal discussing the stereotyped ”double negative”--being a fat lesbian learning strategies of resistance to societal ideals critiquing ”the culture of desire” within gay men’s communities that emphasizes looks above everything else Revealing new and complex dimensions to body image issues, Looking Queer not only discusses the struggles and hardships of gay, lesbian, bisexual, and transgendered persons, but looks at the processes that can lead to acceptance of oneself. Written by both men and women, the topics and research in Looking Queer offer insight into the lives of people you can relate to, enabling you to learn from their experiences so you, too, can find joy and happiness in accepting your body.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; image corporelle; intersectionnalité; premier cycle; queer; régions géographiques; sciences humaines; soc2014; thématiques; troubles alimentaires; états-unis

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

« Oppression, » dans The politics of reality, - Frye, Marilyn (The politics of reality: essays in feminist theory, 1983)
Politics of Reality includes nine essays that examine sexism, the exploitation of women, the gay rights movement and other topics from a feminist perspective. The essays "The Problem That Has No Name" and "A Note On Anger" have been translated into Spanish by Maria Lugones for circulation in la Asociacion Argentina de Mujeres en Filosofia.
Keywords: 1900-1999; 1970-1979; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; identités LGBTQIA2+; intersectionnalité; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Luttes féministes plurielles face à un patriarcat global - Institut de recherches et d'études féministes
Dans cet épisode, on vous emmène en immersion dans plusieurs ateliers où s'entrelacent luttes intersexes, féminismes, enjeux religieux et mobilisations de terrain. Entre rencontres avec la Table des groupes de femmes de Montréal, participation à des discussions sur les droits intersexes, et réflexions autour du féminisme et de la religion, on explore une question centrale : comment les personnes en lutte féministes, intersexes, marginalisées parviennent-elles à faire valoir leurs droits au quotidien ? À travers des initiatives comme Hoodstock et des approches comme la défense collective des droits, on découvre comment se construisent des fronts communs mais aussi pour qui ils sont véritablement bénéfiques, et à qui ils profitent moins. Avec: Marie-Andrée Roy, Cassandra Exumé, Dalila Awada, Table des groupes de femmes de Montréal, Janik Bastien Charlebois Épisode enregistré durant la Foire féministe de l'IREF (27, 28 février et 1er mars 2025 - https://sites.grenadine.uqam.ca/sites/dsj/fr/foire-feministe-feministes-dans-la-cite) . Monté et écrit par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; LGBTQIA2+; amérique; approches et analyses; discipline; discours dominant; droit; droits des femmes*; foire féministe; intersectionnalité; intersexe; périodes historiques; québec; régions géographiques; science des religions; systèmes d'oppressions; thématiques